Preparation method of aluminum oxide hydrogen-resistant coating on zirconium hydride surface

The aluminum-oxide hydrogen-resistance coating was prepared by magnetron sputtering aluminum plating and microarc oxidation method, which solved the problem of hydrogen dissipation of zirconium hydride, and formed a dense and closely bound to the matrix, which significantly improved the hydrogen resistance and service life of zirconium hydride.

CN119913587APending Publication Date: 2025-05-02ZHONGYUAN CRITICAL METAL LAB
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510115192.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Zirconium hydride is prone to hydrogen evolution reactions under specific environments, reducing the neutron slowing efficiency and shortening the service life. The prior art hydrogen resistance coating has a thin thickness and is not ideal in binding force, which affects its hydrogen resistance performance.

Method used

Aluminum-resistant hydrogen coating is prepared by magnetron sputtering and microarc oxidation method to form a composite structural coating composed of a dense layer and a loose layer to enhance the bonding force with the substrate and hydrogen resistance effect.

Benefits of technology

The formed alumina film layer has good anti-hydrogen permeability, improves the hydrogen resistance of zirconium hydride and extends its service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119913587A_ABST
    Figure CN119913587A_ABST
Patent Text Reader

Abstract

The preparation method of the aluminum oxide hydrogen-resistant coating on the zirconium hydride surface disclosed by the embodiment of the invention comprises the following steps: S1, plating aluminum on the surface of a zirconium hydride matrix in a magnetron sputtering manner, and forming an aluminum film on the surface of the zirconium hydride matrix; and S2, the aluminum film formed on the surface of the zirconium hydride matrix is subjected to micro-arc oxidation to obtain aluminum oxide, and the aluminum oxide hydrogen-resistant coating is obtained. Wherein an aluminum oxide film layer formed on the surface of zirconium hydride is tightly combined with a zirconium hydride matrix, and the thickness of the film layer is 5-80 microns; the aluminum oxide film layer is composed of an inner compact layer with a non-porous structure and an outer loose layer with a closed pore structure, the thickness of the compact layer is 2-15 microns, and the compact layer has a good hydrogen permeation resistance effect; the aluminum oxide film layer on the surface of zirconium hydride can serve as an aluminum oxide hydrogen-resistant coating, the hydrogen-resistant capacity of the zirconium hydride moderator is improved, and the service life of the zirconium hydride moderator is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material surface treatment, and in particular relates to a method for preparing an aluminum oxide hydrogen barrier coating on the surface of zirconium hydride. Background Art

[0002] Zirconium hydride has a high hydrogen density, low neutron capture cross section, negative temperature coefficient, good thermal stability, thermal conductivity and processing performance, and is an ideal solid neutron moderator material. Zirconium hydride, as a nuclear reactor power source for moderators, can provide long-term reliable and high-power energy. However, zirconium hydride is prone to hydrogen evolution reaction under certain conditions, which will reduce the neutron moderation efficiency and shorten its service life.

[0003] A ceramic coating with low hydrogen diffusion coefficient and low surface composite constant is prepared on the surface of zirconium hydride by surface treatment technology. The ceramic coating can effectively prevent the precipitation of hydrogen in the matrix zirconium hydride as a hydrogen permeation barrier, thereby extending the service life of the zirconium hydride moderator. This method benefits from the fact that the diffusion rate of hydrogen in ceramic materials is much lower than its diffusion rate in metals. Hydrogen permeation barrier film materials are mainly divided into two categories: oxide film layers and non-oxide film layers.

[0004] In the prior art, a hydrogen barrier coating can be prepared by electroplating chromium on the surface of pre-oxidized zirconium hydride. However, the electroplating process conditions have a great influence on the morphology of the hydrogen barrier coating. The current density will affect the pores and cracks of the hydrogen barrier coating. Therefore, the electroplating process conditions and the characterization of the anti-hydrogen permeation layer need further study. An in-situ oxidation method can be used to prepare an oxide hydrogen barrier coating on the surface of zirconium hydride under atmosphere conditions such as oxygen, carbon dioxide, and water vapor. However, the in-situ oxidation method has certain limitations, and the thickness of the coating obtained is relatively thin, and the hydrogen barrier effect in practical applications is not satisfactory. Spraying technology can also be used to prepare Al 2 O 3 -40% 7YSZ coating, but the spraying technology has high requirements on the spraying materials and often requires complex processes such as granulation, which limits its wide application. In addition, the bonding strength between the prepared coating and the substrate is not very ideal, and the effective service life and hydrogen barrier performance are limited. Summary of the invention

[0005] In view of this, the technical solution disclosed in some embodiments is a method for preparing an aluminum oxide hydrogen barrier coating on the surface of zirconium hydride, comprising the steps of:

[0006] S1. The surface of the zirconium hydride substrate is coated with aluminum by magnetron sputtering to form an aluminum film on the surface of the zirconium hydride substrate;

[0007] S2. The aluminum film formed on the surface of the zirconium hydride substrate is micro-arc oxidized into aluminum oxide to obtain an aluminum oxide hydrogen barrier coating.

[0008] Further, in some embodiments, the method for preparing the aluminum oxide hydrogen barrier coating on the surface of zirconium hydride disclosed in step S1 comprises:

[0009] The magnetron sputtering vacuum chamber was evacuated to a vacuum degree of 1.0×10 -4 ~8.5×10 -4 Pa, heat the vacuum chamber to a temperature of 25-200°C and keep it warm for 5-120 minutes;

[0010] Argon gas is introduced into the magnetron sputtering vacuum chamber until the pressure in the vacuum chamber reaches 2-7 Pa, and then the zirconium hydride substrate is back-splash cleaned for 5-20 minutes;

[0011] Adjust the sputtering target power to 50-200W, control the argon gas flow rate to 50-100ml / min, and perform pre-sputtering for 2-15min;

[0012] Then, sputtering coating is performed with the sputtering time being 50 to 150 minutes to obtain an aluminum film on the zirconium hydride substrate.

[0013] In the method for preparing the aluminum oxide hydrogen barrier coating on the surface of zirconium hydride disclosed in some embodiments, after the sputtering coating is completed in step S1, the temperature is adjusted to 20-180° C. and kept warm for 0.5-10 hours;

[0014] In some embodiments, the method for preparing the aluminum oxide hydrogen barrier coating on the surface of zirconium hydride disclosed in step S2 comprises:

[0015] A zirconium hydride substrate coated with an aluminum film is used as an anode, and an electrolyte solution containing sodium polyphosphate, sodium hydroxide and disodium ethylenediaminetetraacetic acid is used as an electrolyte to perform micro-arc oxidation treatment, so that the aluminum film on the surface of the zirconium hydride substrate is converted into an aluminum oxide coating; wherein the forward voltage of the micro-arc oxidation power supply is 150 to 350 V, the negative voltage is 35 to 400 V, the frequency is 50 to 450 Hz, and the treatment time is 1 to 50 minutes.

[0016] Some embodiments disclose a method for preparing an aluminum oxide hydrogen barrier coating on the surface of zirconium hydride. In step S2, in the electrolyte solution, the concentration of sodium hydroxide is 0.5 to 15 g / L, the concentration of sodium polyphosphate is 3 to 32 g / L, and the concentration of disodium ethylenediaminetetraacetate is 1 to 6 g / L.

[0017] Some embodiments disclose a method for preparing an aluminum oxide hydrogen barrier coating on the surface of zirconium hydride. In step S2, micro-arc oxidation treatment is performed in a stainless steel electrolytic cell, and the stainless steel electrolytic cell is provided with circulating water for cooling to control the micro-arc oxidation treatment to be performed at room temperature.

[0018] In the method for preparing the aluminum oxide hydrogen barrier coating on the surface of zirconium hydride disclosed in some embodiments, step S1 also includes a pretreatment step for the zirconium hydride substrate, specifically including:

[0019] The surface of the zirconium hydride substrate is polished step by step using water sandpaper;

[0020] The zirconium hydride substrate is placed in an acetone and anhydrous ethanol solution for ultrasonic cleaning;

[0021] The acetone solution remaining on the surface of the zirconium hydride substrate is then cleaned with deionized water.

[0022] In the method for preparing the aluminum oxide hydrogen barrier coating on the surface of zirconium hydride disclosed in some embodiments, the thickness of the aluminum oxide hydrogen barrier coating formed on the surface of the zirconium hydride substrate is 5 to 80 μm.

[0023] The method for preparing the aluminum oxide hydrogen barrier coating on the surface of zirconium hydride disclosed in an embodiment of the present invention forms an aluminum oxide film layer tightly bonded to the surface of a substrate on the surface of the zirconium hydride, and the thickness of the film layer is 5 to 80 μm; the aluminum oxide film layer consists of an inner layer of a dense layer with a non-porous structure and an outer layer of a loose layer with a closed pore structure, wherein the dense layer has a thickness of 2 to 15 μm and has good resistance to hydrogen penetration; the aluminum oxide film layer on the surface of the zirconium hydride can be used as an aluminum oxide hydrogen barrier coating, thereby improving the hydrogen barrier ability of the zirconium hydride moderator and extending the service life of the zirconium hydride moderator. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is the hydrogen permeability factor value of the aluminum film layer on the surface of zirconium hydride and the aluminum oxide hydrogen barrier coating disclosed in Examples 1 to 3;

[0025] Figure 2 This is the surface morphology of the hydrogen barrier coating on the zirconium hydride surface disclosed in Example 3. DETAILED DESCRIPTION

[0026] The word "embodiment" used herein as an "exemplary" does not necessarily mean that any embodiment described is superior or better than other embodiments. Performance index tests in the embodiments of the present invention are performed using conventional test methods in the art unless otherwise specified. It should be understood that the terms described in the embodiments of the present invention are only used to describe specific implementation methods and are not intended to limit the contents disclosed in the embodiments of the present invention.

[0027] Unless otherwise specified, the technical and scientific terms used herein have the same meanings as commonly understood by ordinary technicians in the technical field to which the embodiments of the present invention belong; other experimental methods and technical means not specifically specified in the embodiments of the present invention refer to experimental methods and technical means commonly used by ordinary technicians in the field.

[0028] The terms "substantially" and "approximately" used herein are used to describe small fluctuations. For example, they can refer to less than or equal to ±5%, such as less than or equal to ±2%, such as less than or equal to ±1%, such as less than or equal to ±0.5%, such as less than or equal to ±0.2%, such as less than or equal to ±0.1%, such as less than or equal to ±0.05%. The numerical data represented or presented in the range format herein are used only for convenience and brevity, and should therefore be flexibly interpreted as including not only the values ​​clearly listed as the limits of the range, but also all independent values ​​or sub-ranges contained in the range. For example, the numerical range of "1-5%" should be interpreted as including not only the clearly listed values ​​of 1% to 5%, but also the independent values ​​and sub-ranges within the range shown. Therefore, independent values ​​such as 2%, 3.5% and 4% and sub-ranges such as 1%-3%, 2%-4% and 3%-5% are included in this numerical range. This principle also applies to the range of only one numerical value. In addition, such an interpretation applies regardless of the width of the range or the characteristics described.

[0029] In this document, including in the claims, transitional words such as "comprises," "includes," "with," "having," "containing," "involving," "accommodating," etc. are understood to be open-ended, i.e., meaning "including but not limited to." Only the transitional words "consisting of" and "composed of" are closed transitional words.

[0030] In order to better illustrate the present invention, numerous specific details are provided in the specific examples below. It should be understood by those skilled in the art that the present invention can be implemented without certain specific details. In the embodiments, some methods, means, instruments, equipment, etc. well known to those skilled in the art are not described in detail in order to highlight the gist of the present invention.

[0031] Under the premise of no conflict, the technical features disclosed in the embodiments of the present invention may be arbitrarily combined, and the resulting technical solutions belong to the contents disclosed in the embodiments of the present invention.

[0032] In some embodiments, the method for preparing the aluminum oxide hydrogen barrier coating on the surface of zirconium hydride comprises the steps of:

[0033] S1. Aluminum is plated on the surface of the zirconium hydride substrate by magnetron sputtering to form an aluminum film on the surface of the zirconium hydride substrate; specifically comprising:

[0034] Pretreating the zirconium hydride substrate, specifically comprising: grinding the surface of the zirconium hydride substrate step by step with water sandpaper; ultrasonically cleaning the zirconium hydride substrate in an acetone and anhydrous ethanol solution; and then cleaning the acetone solution remaining on the surface of the zirconium hydride substrate with deionized water;

[0035] The magnetron sputtering vacuum chamber was evacuated to a vacuum degree of 1.0×10 -4 ~8.5×10-4 Pa, heat the vacuum chamber to a temperature of 25-200°C and keep it warm for 5-120 minutes;

[0036] Argon gas is introduced into the magnetron sputtering vacuum chamber until the pressure in the vacuum chamber is 2-7 Pa, and then the pre-treated zirconium hydride substrate is back-splash cleaned for 5-20 minutes. Generally, the back-splash cleaning process can activate the surface atoms of zirconium hydride, which is beneficial to the interaction with aluminum atoms in the subsequent aluminum plating process, so that the aluminum film layer and the zirconium hydride substrate are more closely combined; at the same time, the surface roughness of zirconium hydride can be improved, which is beneficial to increase the contact area between the aluminum film and the zirconium hydride substrate and improve the adhesion of the aluminum film.

[0037] Adjust the sputtering target power to 50-200W, control the argon gas flow rate to 50-100ml / min, and perform pre-sputtering for 2-15min;

[0038] Then, sputtering coating is performed, and the sputtering time is 50 to 150 minutes to form an aluminum film on the zirconium hydride substrate;

[0039] After the sputtering coating is completed, adjust the temperature to a suitable range of 20 to 180°C and keep it warm for 0.5 to 10 hours;

[0040] S2. The aluminum film formed on the surface of the zirconium hydride substrate is micro-arc oxidized into aluminum oxide to obtain an aluminum oxide hydrogen barrier coating; specifically comprising:

[0041] A zirconium hydride substrate coated with an aluminum film is used as an anode, and an electrolyte solution containing sodium polyphosphate, sodium hydroxide and disodium ethylenediaminetetraacetic acid is used as an electrolyte, and the electrolyte is placed in a stainless steel electrolytic cell; the zirconium hydride substrate anode coated with an aluminum film is placed in the electrolyte, and the stainless steel electrolytic cell is used as a cathode to perform micro-arc oxidation treatment, so that the aluminum film on the surface of the zirconium hydride substrate is converted into an aluminum oxide coating; wherein the stainless steel electrolytic cell is provided with circulating water cooling to control the micro-arc oxidation treatment to be performed at room temperature, the forward voltage of the micro-arc oxidation power supply is 150-350V, the negative voltage is 35-400V, the frequency is 50-450Hz, and the treatment time is 1-50min; wherein, in the electrolyte solution, the concentration of sodium hydroxide is 0.5-15g / L, the concentration of sodium polyphosphate is 3-32g / L, and the concentration of disodium ethylenediaminetetraacetic acid is 1-6g / L; and the thickness of the aluminum oxide hydrogen barrier coating formed on the surface of the zirconium hydride substrate is 5-80μm.

[0042] The aluminum oxide film layer formed on the surface of zirconium hydride is tightly bonded to the substrate surface, and the thickness of the aluminum oxide film layer is 5 to 80 μm; the aluminum oxide film layer is composed of an inner layer of a dense layer with a non-porous structure and an outer layer of a loose layer with a closed pore structure, wherein the dense layer is 2 to 15 μm thick and has good resistance to hydrogen penetration; the aluminum oxide film layer on the surface of zirconium hydride can serve as an aluminum oxide hydrogen barrier coating, thereby improving the hydrogen barrier ability of the zirconium hydride moderator and extending the service life of the zirconium hydride moderator.

[0043] The technical details are further illustrated below in conjunction with embodiments.

[0044] Example 1

[0045] The method for preparing the aluminum oxide hydrogen barrier coating on the surface of zirconium hydride disclosed in Example 1 comprises:

[0046] ZrH 1.8 The raw material was cut into φ20mm×3mm slices as zirconium hydride matrix samples;

[0047] The surface and corners of the zirconium hydride matrix sample were mechanically polished step by step with 360#, 600#, 800# and 1000# SiC water sandpaper respectively; the zirconium hydride matrix sample was ultrasonically cleaned in acetone solution for 15 minutes, then cleaned with deionized water to remove the residual acetone solution on the surface, and dried;

[0048] The pretreated zirconium hydride matrix sample was placed on the sample table in the magnetron sputtering vacuum chamber, and the vacuum chamber was evacuated. When the vacuum degree reached 1.0×10 -4 Pa, heat the vacuum chamber to 25°C and then keep it warm for 5 minutes;

[0049] Argon gas was introduced into the vacuum chamber, and when the pressure in the vacuum chamber was 2 Pa, the surface of the zirconium hydride substrate sample was backsplash cleaned for 5 minutes;

[0050] Apply 50W sputtering power to the aluminum target, control the argon flow rate at 50ml / min, and pre-sputter for 2min;

[0051] The zirconium hydride substrate sample was sputtered for 50 minutes;

[0052] After the sputtering coating stops, the temperature is adjusted to 20°C, and after keeping the temperature for 0.5h, the vacuum chamber is cooled to room temperature to obtain a zirconium hydride substrate sample coated with an aluminum film;

[0053] A WHD30 power supply is applied to a stainless steel electrolytic cell, and a zirconium hydride substrate sample is placed as an anode in a stainless steel electrolytic cell containing an electrolyte for micro-arc oxidation treatment. The temperature of the micro-arc oxidation electrolyte is controlled at room temperature to generate an aluminum oxide coating. A thermometer is provided in the stainless steel electrolytic cell for temperature indication, and circulating water is passed through the stainless steel electrolytic cell. The concentration of sodium hydroxide in the electrolyte is 0.5 g / L, the concentration of sodium polyphosphate is 3 g / L, and the concentration of disodium EDTA is 1 g / L. The forward voltage of the micro-arc oxidation power supply is 150 v, the negative voltage is 400 v, the frequency is 50 Hz, and the treatment time is 1 min.

[0054] The cross section of the obtained zirconium hydride coating was analyzed by scanning electron microscopy. The results showed that the obtained zirconium hydride coating was a composite structure coating, which was dense and firmly bonded to the zirconium hydride substrate. The composite structure coating included an inner non-porous structure dense layer and an outer closed pore structure loose layer; the thickness of the dense layer was about 2μm, and the thickness of the composite structure coating was about 18μm; Figure 1 As shown, the PRF value of the zirconium hydride matrix sample in Example 1 is 17.4, and the vacuum dehydrogenation test is used to test the hydrogen barrier effect of the aluminum oxide coating prepared in Example 1. The results show that the zirconium hydride matrix sample with zirconium oxide coating obtained in Example 1 has a hydrogen loss mass percentage of less than 3.2% and a PRF value of 22.3, indicating that the composite structural coating obtained by the expansion ratio has a good hydrogen barrier effect.

[0055] Example 2

[0056] The method for preparing the aluminum oxide hydrogen barrier coating on the surface of zirconium hydride disclosed in Example 2 comprises:

[0057] ZrH 1.8 The raw material was cut into φ20mm×3mm slices as zirconium hydride matrix samples;

[0058] The surface and corners of the zirconium hydride matrix sample were mechanically polished step by step with 360#, 600#, 800# and 1000# SiC water sandpaper respectively; the zirconium hydride matrix sample was ultrasonically cleaned in acetone solution for 15 minutes, then cleaned with deionized water to remove the residual acetone solution on the surface, and dried;

[0059] The pretreated zirconium hydride matrix sample was placed on the sample stage in the magnetron sputtering vacuum chamber, and the vacuum chamber was evacuated. When the vacuum degree reached 4.5×10 -4 Pa, heat the vacuum chamber to 110°C and then keep it warm for 60 minutes;

[0060] Argon gas was introduced into the vacuum chamber, and when the pressure in the vacuum chamber was 4.5 Pa, the surface of the zirconium hydride substrate sample was backsplash cleaned for 12 minutes;

[0061] Apply 125W sputtering power to the aluminum target, control the argon flow rate at 75ml / min, and pre-sputter for 8min;

[0062] The zirconium hydride substrate sample was sputtered for 100 minutes;

[0063] After the sputtering coating stops, the temperature is adjusted to 100°C, and after keeping the temperature for 5 hours, the vacuum chamber is cooled to room temperature to obtain a zirconium hydride substrate sample coated with an aluminum film;

[0064] A WHD30 power supply is applied to a stainless steel electrolytic cell, and a zirconium hydride substrate sample is placed as an anode in a stainless steel electrolytic cell containing an electrolyte for micro-arc oxidation treatment. The temperature of the micro-arc oxidation electrolyte is controlled at room temperature to generate an aluminum oxide coating. A thermometer is provided in the stainless steel electrolytic cell for temperature indication, and circulating water is passed through the stainless steel electrolytic cell. The concentration of sodium hydroxide in the electrolyte is 0.5 g / L, the concentration of sodium polyphosphate is 3 g / L, and the concentration of disodium EDTA is 1 g / L. The forward voltage of the micro-arc oxidation power supply is 150 v, the negative voltage is 400 v, the frequency is 50 Hz, and the treatment time is 1 min.

[0065] The cross section of the obtained zirconium hydride coating was analyzed by scanning electron microscopy. The results showed that the obtained zirconium hydride coating was a composite structure coating, which was dense and firmly bonded to the zirconium hydride substrate. The composite structure coating included an inner non-porous structure dense layer and an outer closed pore structure loose layer; the thickness of the dense layer was about 8μm, and the thickness of the composite structure coating was about 30μm; Figure 1 As shown, in Example 2, the PRF value of the zirconium hydride matrix sample is 16.9, and the vacuum dehydrogenation test is used to test the hydrogen barrier effect of the aluminum oxide coating prepared in Example 2. The results show that the zirconium hydride matrix sample with zirconium oxide coating obtained in Example 2 has a hydrogen loss mass percentage of less than 2.5% and a PRF value of 25.1, indicating that the composite structure coating obtained with a shrinkage rate of 2 has a good hydrogen barrier effect.

[0066] Example 3

[0067] The method for preparing the aluminum oxide hydrogen barrier coating on the surface of zirconium hydride disclosed in Example 3 comprises:

[0068] ZrH 1.8 The raw material was cut into φ20mm×3mm slices as zirconium hydride matrix samples;

[0069] The surface and corners of the zirconium hydride matrix sample were mechanically polished step by step with 360#, 600#, 800# and 1000# SiC water sandpaper respectively; the zirconium hydride matrix sample was ultrasonically cleaned in acetone solution for 15 minutes, then cleaned with deionized water to remove the residual acetone solution on the surface, and dried;

[0070] The pretreated zirconium hydride matrix sample was placed on the sample table in the magnetron sputtering vacuum chamber, and the vacuum chamber was evacuated. When the vacuum degree reached 8.5×10 -4 Pa, heat the vacuum chamber to 200°C and then keep it warm for 120 min;

[0071] Argon gas was introduced into the vacuum chamber, and when the pressure in the vacuum chamber was 7 Pa, the surface of the zirconium hydride substrate sample was backsplash cleaned for 20 minutes;

[0072] Apply a sputtering power of 200 W to the aluminum target, control the argon flow rate at 100 ml / min, and pre-sputter for 15 minutes;

[0073] The zirconium hydride substrate sample was sputtered for 150 minutes;

[0074] After the sputtering coating stops, the temperature is adjusted to 180°C, and after keeping the temperature for 10 hours, the vacuum chamber is cooled to room temperature to obtain a zirconium hydride substrate sample coated with an aluminum film;

[0075] A WHD30 power supply is applied to a stainless steel electrolytic cell, and a zirconium hydride substrate sample is placed as an anode in a stainless steel electrolytic cell containing an electrolyte for micro-arc oxidation treatment. The temperature of the micro-arc oxidation electrolyte is controlled at room temperature to generate an aluminum oxide coating. A thermometer is provided in the stainless steel electrolytic cell for temperature indication, and circulating water is passed through the stainless steel electrolytic cell. The concentration of sodium hydroxide in the electrolyte is 15 g / L, the concentration of sodium polyphosphate is 32 g / L, and the concentration of disodium EDTA is 6 g / L. The forward voltage of the micro-arc oxidation power supply is 500 V, the negative voltage is 35 V, the frequency is 450 Hz, and the treatment time is 50 min.

[0076] The morphology of the zirconium hydride coating was analyzed using a scanning electron microscope. Figure 2 As shown, the results show that the film layer is flat. The cross-section of the obtained zirconium hydride coating was analyzed using a scanning electron microscope. The results show that the obtained zirconium hydride coating is a composite structure coating, including an inner layer of a non-porous structure dense layer and an outer layer of a closed pore structure loose layer, and the coating thickness is about 67μm; the composite structure coating is dense, the dense layer thickness is about 15μm, and it is firmly bonded to the zirconium hydride substrate; Figure 1 As shown, in Example 3, the PRF value of the zirconium hydride matrix sample is 18.2, and the vacuum dehydrogenation test is used to test the hydrogen barrier effect of the aluminum oxide coating prepared in Example 3. The results show that the zirconium hydride matrix sample with zirconium oxide coating obtained in Example 3 has a hydrogen loss mass percentage of less than 2% and a PRF value of 27.3, indicating that the composite structural coating obtained in Example 3 has a good hydrogen barrier effect.

[0077] The method for preparing the aluminum oxide hydrogen barrier coating on the surface of zirconium hydride disclosed in an embodiment of the present invention forms an aluminum oxide film layer tightly bonded to the surface of a substrate on the surface of the zirconium hydride, and the thickness of the film layer is 5 to 80 μm; the aluminum oxide film layer consists of an inner layer of a dense layer with a non-porous structure and an outer layer of a loose layer with a closed pore structure, wherein the dense layer has a thickness of 2 to 15 μm and has good resistance to hydrogen penetration; the aluminum oxide film layer on the surface of the zirconium hydride can be used as an aluminum oxide hydrogen barrier coating, thereby improving the hydrogen barrier ability of the zirconium hydride moderator and extending the service life of the zirconium hydride moderator.

[0078] The technical solutions disclosed in the embodiments of the present invention and the technical details disclosed in the embodiments are merely illustrative of the inventive concept of the present invention and do not constitute a limitation on the technical solutions of the embodiments of the present invention. Any conventional changes, replacements or combinations of the technical details disclosed in the embodiments of the present invention have the same inventive concept as the present invention and are within the protection scope of the claims of the present invention.

Claims

1. A method for preparing an aluminum oxide hydrogen barrier coating on the surface of zirconium hydride, characterized in that: Includes steps: S1. The surface of the zirconium hydride substrate is coated with aluminum by magnetron sputtering to form an aluminum film on the surface of the zirconium hydride substrate; S2. The aluminum film formed on the surface of the zirconium hydride substrate is micro-arc oxidized into aluminum oxide to obtain an aluminum oxide hydrogen barrier coating.

2. The method for preparing the aluminum oxide hydrogen barrier coating on the surface of zirconium hydride according to claim 1, characterized in that: Step S1 includes: The magnetron sputtering vacuum chamber was evacuated to a vacuum degree of 1.0×10 -4 ~8.5×10 -4 Pa, heat the vacuum chamber to a temperature of 25-200°C and keep it warm for 5-120 minutes; Argon gas is introduced into the magnetron sputtering vacuum chamber until the pressure in the vacuum chamber reaches 2-7 Pa, and then the zirconium hydride substrate is back-splash cleaned for 5-20 minutes; Adjust the sputtering target power to 50-200W, control the argon gas flow rate to 50-100ml / min, and perform pre-sputtering for 2-15min; Then, sputtering coating is performed with the sputtering time being 50 to 150 minutes to obtain an aluminum film on the zirconium hydride substrate.

3. The method for preparing the aluminum oxide hydrogen barrier coating on the surface of zirconium hydride according to claim 2, characterized in that: After the sputtering coating is completed in step S1, the temperature is adjusted to between 20 and 180° C. and kept warm for 0.5 to 10 hours.

4. The method for preparing the aluminum oxide hydrogen barrier coating on the surface of zirconium hydride according to claim 1, characterized in that: Step S2 includes: A zirconium hydride substrate coated with an aluminum film is used as an anode, and an electrolyte solution containing sodium polyphosphate, sodium hydroxide and disodium ethylenediaminetetraacetic acid is used as an electrolyte to perform micro-arc oxidation treatment, so that the aluminum film on the surface of the zirconium hydride substrate is converted into an aluminum oxide coating; wherein the forward voltage of the micro-arc oxidation power supply is 150 to 350 V, the negative voltage is 35 to 400 V, the frequency is 50 to 450 Hz, and the treatment time is 1 to 50 minutes.

5. The method for preparing the aluminum oxide hydrogen barrier coating on the surface of zirconium hydride according to claim 4, characterized in that: In step S2, in the electrolyte solution, the concentration of sodium hydroxide is 0.5-15 g / L, the concentration of sodium polyphosphate is 3-32 g / L, and the concentration of disodium ethylenediaminetetraacetate is 1-6 g / L.

6. The method for preparing the aluminum oxide hydrogen barrier coating on the surface of zirconium hydride according to claim 4, characterized in that: In step S2, the micro-arc oxidation treatment is carried out in a stainless steel electrolytic cell, and the stainless steel electrolytic cell is provided with circulating water cooling to control the micro-arc oxidation treatment to be carried out at room temperature.

7. The method for preparing the aluminum oxide hydrogen barrier coating on the surface of zirconium hydride according to claim 1, characterized in that: Step S1 also includes a pretreatment step for the zirconium hydride substrate, specifically including: The surface of the zirconium hydride substrate is polished step by step using water sandpaper; The zirconium hydride substrate is placed in an acetone and anhydrous ethanol solution for ultrasonic cleaning; The acetone solution remaining on the surface of the zirconium hydride substrate is then cleaned with deionized water.

8. The method for preparing the aluminum oxide hydrogen barrier coating on the surface of zirconium hydride according to claim 1, characterized in that: The thickness of the aluminum oxide hydrogen barrier coating formed on the surface of the zirconium hydride substrate is 5-80 μm. The aluminum oxide hydrogen barrier coating consists of an inner non-porous dense layer and an outer closed pore loose layer, wherein the thickness of the dense layer is 2-15 μm.

Citation Information

Cited By

  • Preparation method and application of titanium-based hydrogen-resistant coating structure on surface of metal hydride

    CN121228190A

  • A preparation method and application of a metal hydride surface titanium-based hydrogen barrier coating structure

    CN121228190B